Kelestarian Lingkungan dalam Al-Qur’an: Analisis Pemikiran M. Quraish Shihab dalam Tafsir Al-Misbah - Andika Mubarok (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
Natural viralslot disasters at this time occur because of arbitrary human actions. If you look at the various verses of the Al-Qur'an which regulate human actions so that they do not do arbitrary acts and preserve the environment viralslot. In this regard, this research aims to explain how to interpret the verse on environmental sustainability according to M. Quraish Shihab and how to istinbath the law on environmental sustainability issues. This study uses a qualitative research method based on descriptive analysis of the interpretation of M. Quraish Shihab. The data sources consist of primary sources, namely the interpretation of Al-Misbah and secondary sources, namely other relevant books, and the results of previous research. The results of the study reveal that preserving the environment is a human responsibility as part of an ecosystem, which can be explored from the instructions of the Qur'an which are regulated in sura al-'Araf verse 56 and ar-Rum verses 41-42. Preserving nature is important because it is a place to live, a source of sustenance, or a means of upbringing to God. Humans on earth as caliphs are obliged to maintain the balance of the universe that Allah created. Environmental damage factor due to two factors, namely internal factors and external factors. Reflections on Quraish Shihab's thoughts are manifested in living cleanly, not littering, recycling waste, and planting trees for sustainable life viralslot.